(untitled) (Journal of science and technology exploration, 2026)
This article is based on the background of the digital transformation of sports, aiming to systematically sort out the innovative practices and integration paths of sports technology in multiple fields, in order to provide reference for promoting the development of sports research and application. The study first explains the inevitability of digital technology driving the paradigm transformation of sports science, and then constructs the core system of digital sports technology around four pillars: sports physiological and biochemical monitoring, intelligent intervention and health care, sports big data and artificial intelligence applications, and intelligent equipment and scene research and development. On this basis, the article combines special sports digitalization, emerging therapy applications, sports for special populations, and industrial ecology to analyze the current progress and challenges. Finally, countermeasures and suggestions are proposed from the aspects of strengthening top-level policy design, deepening the integration of industry, academia, and research, strengthening ethical and data governance, and promoting inclusive development, in order to provide theoretical support and practical guidance for building a higher-level public service system for national fitness and serving the Healthy China strategy.